Cation Sensing Capabilities of A Nitrophenyl Cinnamaldehyde Derivative - Suryanti, Venty; Wibowo, Fajar Rakhman; Marzuki, Ahmad; Sari, Meiyanti Ratna Kumala (Molekul, 2020)
The cationic chemosensor based on organic compound bearing an aminophenol moiety as a receptor for metal analyte and a cinnamaldehyde moiety as chromophoric fragment has been developed. In this work, we report the colorimetric sensing of nitrophenyl cinnamaldehyde derivative, namely methyl-3-(2-hidroxy-5-nitrophenyl amino)-3-phenylpropanoate, towards a variety of metal cations, such as Cu2+, Fe3+, Ni2+ and Zn2+. The cation sensing abilities of the sensor were observed for Cu2+and Fe3+ with a color change from colorless to pink and faint yellow, respectively, The characteristic UV-Vis spectra changes were observed upon addition of Cu2+and Fe3+ cations. The hypsochromic absorption spectra shifts were obtained, indicating the cations and sensor complexations had formed. A metal-to-ligand-charge-transfer (MLCT) had occurred and the charge density of the sensor changed resulting in appearance of new absorption peaks in the UV-Vis spectra and color changes of the sensor solution upon addition of the Cu2+and Fe3+. Â